PENDIDIKAN AGAMA ISLAM DALAM DINAMIKA POLITIK KEBANGSAAN DI INDONESIA - Dwi Noviani; Firmansyah Firmansyah (Hijri, 2021)
The existence of Islamic education in Indonesia is a fact that has been going on for a very long time and has become popular in the community. During the Dutch colonial period and the Japanese population, education was organized by the community itself by establishing Islamic boarding schools, schools and other places for training. After independence, Islamic education with the characteristics of madrasas and pesantren began to get attention and guidance from the government of the Republic in Indonesia. In the laws of the Republic of Indonesia, UUDRI No. 20 of 2002, and UUDRI No. 13 of 2014 and then implemented in the national education curriculum. It is hoped that the birth of this law will be able to raise the quality of education in bringing prosperity and progress to the Indonesian people.Keywords:Keterampilan Dasar, Pembelajaran, Guru